Entropy and Time Arrow in Aerophysics, Plasma dynamics and Quantum Mechanics - Ivanov, Mikhail Ja.; Mamaev, Vadim K.; Serov, Yuriy L. (Physics of Entropy, Radiation and Gravitating Matter with Examples of General and Analytical Solutions, 2021)
The nature of entropy connection with time arrow (i.e. the irreversibility of time) in some technical problems is analyzed. Entropy is considered as a state function of nature dominant radiate medium. The consideration allows introducing the full thermo dynamical gaseous medium description. Dominant radiate medium in the nature has temperature, pressure, density, internal energy and a finite particle mass. A complete system of conservation laws of mass, momentum and energy is written for two component medium of air and radiation. For confirmation this classical gaseous simulation the special experimental study on registration of pressure in the technical vacuum conditions has been fulfilled by heating of the metal sealed container (with volume near half liter) at temperature range from 300 K to 1530 K. The last part of the paper considers the irreversible time dynamics in physical, chemical and plasma problems.